(untitled) (Third Sector Social Economic Review, 2026)
The growing environmental crises, social inequalities, and demands for corporate transparency on a global scale have shifted traditional governance into a new perspective. This study conceptually examines corporate governance within the framework of sustainability and ESG (Environmental, Social, Governance) dimensions and discusses the future orientations of this integration. Although these concepts have often been studied separately in the literature, limited attention has been given to integrating them with theoretical foundations and evaluating them within a forward-looking vision. The research was designed as a qualitative review, systematically analyzing national and international reports, regulations, and academic literature. In this context, sustainability was addressed through its economic, environmental, and social dimensions; corporate risk management, social responsibility, and long-term value creation were analyzed within the framework of the Brundtland Report and the United Nations 2030 Sustainable Development Goals. Furthermore, the relationship between ESG and corporate governance was discussed, focusing on how reporting standards and performance criteria influence investor decisions, corporate reputation, competitive advantage, and financial outcomes. The findings reveal that sustainability and ESG have become a new standard for corporate governance today. The originality of this study lies in its treatment of corporate governance not only as a current transformation but also as a dynamic paradigm that will integrate with ethical values, digitalization, and innovation-oriented trends in the future. In this respect, the study makes a conceptual contribution to the literature and serves as a strategic roadmap for businesses and policymakers.